SAT0130 TREAT-TO-TARGET STRATEGY OF >8.000 PATIENTS WITH EARLY RHEUMATOID ARTHRITIS: DOES SMOKING AFFECT ACHIEVEMENT OF REMISSION ON METHOTREXATE AND TIME TO START OF FIRST BIOLOGIC? RESULTS FROM THE NATIONWIDE DANISH DANBIO REGISTRY. (2nd June 2020) - Glintborg, B.; Hendricks, O.; Colic, A.; Lindegaard, H. M.; Ahmed, R.; Loft, A. G.; Kollerup, G.; Andersen, M.; Grydehøj, J.; Raun, J.; Thorgrimsen, T.; Mortensen, K.; et al.
Abstract : Background: Smoking is a known risk factor for rheumatoid arthritis (RA). It is largely unknown whether smoking has any impact on disease activity and treatment outcomes (e.g. achieving remission on methotrexate and time to first biological disease modifying anti-rheumatic treatments (bDMARD)) in early RA with a modern treat-to-target strategy. Objectives: To explore if smoking was associated with treatment outcomes in newly diagnosed patients with RA starting first conventional synthetic (cs)DMARDs in routine care. Methods: Observational cohort study. Adult patients with RA starting first csDMARD during year 2010-2018 were identified in the Danish nationwide quality registry, DANBIO. Smoking status (current/never/previous) upon start of csDMARD (=baseline), disease activity, 1-year treatment outcomes and bDMARD treatment were retrieved from DANBIO. Data were censored Oct 2019. Impact of smoking status was explored for the following outcomes: 1) median baseline disease activity baseline, 2) remission at 1-year (logistic regression analyses), 3) time to first bDMARD (Cox-regression analyses). Regression analyses were adjusted for gender and age. Results: Among 9515 patients, 8647 (91%) had available smoking status (Current 23%/never 50%/previous 27%) and were included. Baseline disease activity was independent of smoking status (Table 1 ). First line csDMARD was methotrexate in 91% of patients. Compared to never smokers, the current smokers were more often men, younger and sero-positive for IgM-RF and anti-CCP. Never and previous smokers had higher odds of remission at 1 year's follow-up compared to current smokers. In adjusted Cox regression analyses, baseline smoking was associated with shorter time to start of first bDMARD (Table 2 ). Conclusion: In this observational study of >8000 patients with RA starting a first csDMARD, current smoking was associated with lower odds of achieving remission on methotrexate and higher chance of having started bMDARD compared to never smokers. Seropositivity may be an intermediate variable. Further analyses are planned to study impact of comorbidities and other confounding factors. Acknowledgments: Thank you to all patients and departments who contribute to the DANBIO registry Disclosure of Interests: Bente Glintborg Grant/research support from: Grants from Pfizer, Biogen and Abbvie, Oliver Hendricks Grant/research support from: Pfizer, MSD, Ada Colic Consultant of: Advisory board Sanofi, Hanne Merete Lindegaard: None declared, Rabiah Ahmed: None declared, Anne Gitte Loft Grant/research support from: Novartis, Consultant of: AbbVie, MSD, Novartis, Pfizer and UCB, Speakers bureau: AbbVie, MSD, Novartis, Pfizer and UCB, Gina Kollerup Speakers bureau: Eli Lilly, Marlene Andersen: None declared, Jolanta Grydehøj: None declared, Johnny Raun: None declared, Toke Thorgrimsen: None declared, Kasper Mortensen: None declared, Line Uhrenholt Speakers bureau: Abbvie, Eli Lilly and Novartis (not related to the submitted work), Dorte Jensen: None declared, Iben Ruge Grant/research support from: Novo Nordisk Foundation, Maren Kalisz: None declared, Kamilla Danebod: None declared, Niels Lomborg: None declared, Niels Steen Krogh: None declared, Merete L. Hetland Grant/research support from: BMS, MSD, AbbVie, Roche, Novartis, Biogen and Pfizer, Consultant of: Eli Lilly, Speakers bureau: Orion Pharma, Biogen, Pfizer, CellTrion, Merck and Samsung Bioepis